Analysis of wholesale egg marketing costs in Colorado - Adolph, Robert Howard, author; Burdick, R. T. (Raymond Terry), 1889-1982, advisor; Gassner, F. X. (Frank X.), committee member; Donaldson, D. N. (David Neill), committee member; Creek, C. Richard, committee member; Voelker, Stanley W., committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Eggs; Farm produce -- Marketing